Algoritma Djikstra : Rute Pengungsian Terpendek Daerah Rawan Bencana di Desa Canggu - Arimbawa K., Ida Bagus Kade Puja (Publisher : Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
Canggu Village, located in North Kuta, Badung Regency, Bali, Indonesia, is a popular tourist area with a population density of 1,305 people per square kilometer. This region offers an attractive combination of natural beauty, rich Balinese culture, and modern lifestyle, yet it also faces high risks of natural disasters such as floods, tsunamis, and coastal erosion due to its coastal location. The coastal geography of Canggu necessitates awareness and preparedness for disasters. This study focuses on formulating and implementing evacuation routes using the Dijkstra algorithm to find the shortest and safest evacuation path from disaster-prone areas to safe zones. The results indicate that the Dijkstra algorithm is effective in establishing evacuation routes from the most vulnerable points, such as Batu Bolong Beach, to safe zones with varying distances, allowing residents to leave high-risk areas quickly and safely. These recommendations are expected to be used by local governments in disaster planning and management.